2015
DOI: 10.1515/nsad-2015-0017
|View full text |Cite
|
Sign up to set email alerts
|

Prisoners' experiences of drug treatment and punishment in four Nordic countries

Abstract: Aims This article describes and analyses prisoners' experiences of drug treatment in prison in four Nordic countries: Denmark, Finland, Norway and Sweden. The article examines how prisoners experience drug treatment, control and sanctions as related to three main topics, namely motivation; the content of the measure and relations to staff; and control and sanctions. Methods & DATA – The article is based on data from twelve prisons, three in each of the four countries; 91 interviews with prisoners; and around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
0
18
0
2
Order By: Relevance
“…Generelt kan man sige, at rusmidler giver erfaringsmaessig, social og følelsesmaessig mening for indsatte i en faengselskontekst. Af samme grund er det et stort spring for mange indsatte at ansøge om at komme i behandling, og studier viser da også, at indsattes motiver for at gå i misbrugsbehandling ofte findes uden for deres aktuelle brug af rusmidler (Giertsen et al, 2015, Kolind, 2012. Mange indsatte ansøger eksempelvis om behandling for at få bedre og blødere afsoningsvilkår.…”
Section: Rusmidler Og Misbrugsbehandling I Faengslerunclassified
“…Generelt kan man sige, at rusmidler giver erfaringsmaessig, social og følelsesmaessig mening for indsatte i en faengselskontekst. Af samme grund er det et stort spring for mange indsatte at ansøge om at komme i behandling, og studier viser da også, at indsattes motiver for at gå i misbrugsbehandling ofte findes uden for deres aktuelle brug af rusmidler (Giertsen et al, 2015, Kolind, 2012. Mange indsatte ansøger eksempelvis om behandling for at få bedre og blødere afsoningsvilkår.…”
Section: Rusmidler Og Misbrugsbehandling I Faengslerunclassified
“…Penalizing visitors and prisoners on the basis of drug violations in prison is a common response internationally and within Australia, perceived as serving the legitimate goal of deterring drug use within prisons (Duke, 2003;Giertsen, Nylander, Frank, & Kolind, 2015;Rodas, Bode, & Dolan, 2012). Restricting physical contact between prisoners and visitors in order to prevent and respond to the trafficking of drugs into prisons is also common (Boudin, Stutz, & Littman, 2013;Cope, 2003;United Kingdom [U.K.] Ministry of Justice, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In many European countries (including Denmark which is the focus of this paper), special wings closed off from the rest of the prison have been established for prisoners in drug treatment programs (European Monitoring Centre for Drugs and Drug Addiction (EMCDDA), 2012; Kolind et al., 2013; Mjåland, 2016). Although there are challenges associated with carrying out drug treatment in prisons (McIntosh and Saville, 2006), research has shown that the staff–prisoner relation in these specialized wings tends to be less authoritarian than in normal prison wings (Kolind et al., 2015; Nylander et al., 2011), and prisoners report that prison life on these wings is less harsh and stressful (Giertsen et al., 2015). On the other hand, the staff in these wings report new dilemmas related to the entry of new categories of treatment staff and the introduction of new treatment-related tasks (Nylander et al., 2011).…”
Section: Introductionmentioning
confidence: 99%